Virtual guided surgery for implant-supported rehabilitation of the edentulous maxilla with immediate loading - Fernandes Tinoco, Eric Jansen (2023)
Objective: present the report of a clinical case of a virtual guided surgery for implant-supported rehabilitation of the edentulous maxilla with immediate loading. Case report: Patient, bi-maxillary edentulous expressed the desire to replace the removable upper total prothesis for a total fixed prothesis on implants. During the clinical evaluation, favorable biological conditions for treatment were observed, such as adequate keratinized tissue band and mild bone resorption. As part of the treatment, the patient was recommended a reverse planning approach, assisted by virtual guided surgery. This involved a prototype surgical guide for the fixation of six dental implants in the maxilla and the installation of an immediate loading protocol prosthesis. Conclusions: The results lead us to conclude that computer-guided virtual surgery for implant-supported prosthetic rehabilitation of the edentulous maxilla with immediate loading, provides a high precision in surgical procedures. It is essential to fabrication of immediate prostheses, represents a minimally invasive alternative, and results in patient satisfaction.